The Validity Analysis of Integration Between Science and Religion in Static Fluid Materials - Santoso, Irsyad Yusuf; Suprapto, Nadi; Hidaayatullaah, Hasan Nuurul; Sanjaya W. S., Mada; Turekhanova, Kunduz (National Dong Hwa University, 2024)
Learning science and religion is a combination of knowledge or science with relevant verses of the Al-Qur’an. Education is not only a means of gaining general knowledge through subjects, but also covers aspects of life as a whole, including religious morals. Considering that natural phenomena are so vast, it would be a shame if students are not given enough integration between science and religion, one of which is in physics lessons. The researcher took the initiative to carry out the application of science and religion further in the hope of providing a solution, namely by teaching physics, fluid material, integrated with verses from the Al-Al-Qur’an. This study employs mixed or combined research (mixed methods) with the type of Explanatory Design. Specifically, data collection and analysis of quantitative data are done in the first stage, and then qualitative data are collected and analyzed in the second stage. The integration of science and religion for the fluid material used produces an average value that is categorized as very good. Apart from that, the material from the validation results uses 3 foundations, namely the theological basis (hadârat an-nas), philosophical basis (hadârat al-falsafah), and scientific basis (hadârat al-'ilm). So that the verses of the Al-Qur’an become the main source of the theological basis for the idea of integration by including religious elements, then the scientific or scientific basis which includes the basics of static fluid physics, and the philosophical basis which includes the field of philosophy to connect these two things.